EFFECTS OF, ATMOSPHERIC HUMIDITY ON DEVELOPING EGGS OF AK GRASSHOPPER, Poekilocerus pictUs (Acridoidea Pyrgomorphidae), AN ARID ZONE SPECIES. - Parihar, D R (Annals of Arid Zone, 2016)
Eggs of Poekilocerus pictus at four developmental stages, viz , _(A) freslaly laid, (B) at germ-band formation, (C) at blastokinesis (c. halfdeveloped) and (D) at postblastokinesis (c. two-thirds developed), were kept at six constant atmospheric humidities (50,60,70,80,90 and 100% R;H.) and at a constant temperature of 31°± 1°C. The nurnidities were controlled in desiccators by various, dilutions of sulphuric acid in water. Freshly laid eggs did not develop at all they shrivelled arid died. The other three stages (B-D} developed normally, and the hatching percentage varied from 75-95.7 without any apparent correlation with humidity. In all the three stages (B-b) the incubation period (from the moment of placing in the,desired the desired constant humidity and at 31°± 1°C. increased with increasing humidity as follows:- ;                              Incubation time (days)                           (for  experimental period)Stages                     Relative Humidity (%)                100      90      80      70      60      50      %B ...            35      39      40      43      45      47      daysC ...            24      27      30      32      35      38        "D  ...           10      11      11      10      12     14         "Eggs of a stage hatched on the same day under the same condition of humidity at tbe given temperature.